GOVERNING CHINA'S ADMINISTRATIVE MONOPOLIES UNDER THE ANTI-MONOPOLY LAW: A TEN-YEAR REVIEW (2008–2018) AND BEYOND. (31st July 2019) - Zhang, Zhanjiang; Wu, Baiding
ABSTRACT: An important focus of China's Anti-Monopoly Law (AML) is "administrative monopolies"—government-imposed restraints on competition. Since adopting the AML in 2008, China gradually has strengthened its efforts to curb administrative monopolies. Despite notable reforms such as the creation of the Fair Competition Review System (FCRS), government restrictions remain a major obstacle to competition in China's economy. The 2008 legislation narrowly defined what constitutes improper government intervention, adopted a permissive standard for determining when public restraints were legitimate, and relied heavily on internal administrative controls to correct infringements. This paper draws upon experience in China and abroad to enhance the ability of China's competition authorities to challenge administrative monopolies. Suggested upgrades include augmenting the robustness of FCRS, introducing new tools to improve competition advocacy, bolstering the ability of competition authorities to initiate or join litigation to attack administrative monopolies, and narrowing the range of justifications that can immunize public restraints.